Proceedings of Motion on Games 2013
DOI: 10.1145/2522628.2522656
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Hand-Over Animation using Principle Component Analysis

Abstract: This paper introduces a method for producing high quality hand motion using a small number of markers. The proposed "handover" animation technique constructs joint angle trajectories with the help of a reference database. Utilizing principle component analysis (PCA) applied to the database, the system automatically determines the sparse marker set to record. Further, to produce hand animation, PCA is used along with a locally weighted regression (LWR) model to reconstruct joint angles. The resulting animation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…A comparison of our marker layout optimization method with the marker subset selection approach of Wheatland et al is shown in Figure . A crucial aspect to note regarding this comparison is that the two methods are based on different marker layout generation paradigms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A comparison of our marker layout optimization method with the marker subset selection approach of Wheatland et al is shown in Figure . A crucial aspect to note regarding this comparison is that the two methods are based on different marker layout generation paradigms.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows that the results of the subset selection method are strongly influenced by the choice of the base marker layout. As the method of Wheatland et al is based on computing an importance ranking for the base markers based on their positional trajectories, the selected marker layouts are clustered around the areas of the hand that move the most in the considered hand motion. In contrast, our method is sensitive to the hand kinematics and the subspace model employed in our approach, which produces layouts that are well suited for subspace‐constrained IK, as opposed to the data‐driven regression approach of Wheatland et al…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hand animation for virtual characters can be reconstructed from image based [Zhao et al 2012;, marker based [Kang et al 2012;Wheatland et al 2013], and glove based [Wang and Neff 2013;Huenerfauth and Lu 2010;Griffin et al 2000;Hu et al 2004;Menon et al 2003;Steffen et al 2011] motion capture techniques, or synthesized using physics knowledge [Zhao et al 2013;Liu 2008;2009;Ye and Liu 2012], data-driven [Jörg et al 2012;ElKoura and Singh 2003] or rule-based methods [Zhu et al 2012]. However, despite all the hand motion acquisition and generation research, little hand motion perception work has been conducted.…”
Section: Related Workmentioning
confidence: 99%